Colorimetric detection of trace amount of Sn(IV) in tap water samples using silver nanoparticles synthesized by clove extract and toxicological risk assessment of these nanoparticles - Zaman, Buse Tugba; Ergenler, Aysegul; Turan, Funda; Bakirdere, Sezgin; Yagmuroglu, Ozan (SPRINGER, 2026)
In our study, a rapid, low-cost analytical method was developed for the colorimetric determination of Sn(IV) using silver nanoparticles (AgNPs) synthesized with clove extract. The AgNPs synthesized have a surface plasmon resonance peak at 425 nm. When Sn(IV) standards at increasing concentrations are added to samples containing AgNPs, a color change proportional to the analyte concentration occurs. With increasing Sn(IV) concentration, the absorbance of the AgNPs decreases. In the analyses, the absorbance change based on analyte concentration was monitored. The detection limit of the developed method was calculated as 7.9 mu M with the linear range as 20-300 mu M. The analytical performance of the method in complex matrix media was demonstrated by conducting recovery experiments in tap water. Our percentage recovery value varies between 97% and 118.0%. The toxicological behavior of the AgNPs were also evaluated in Daphnia magna (D. magna) to justify the safety and ecotoxicity of the synthesized nanoparticles. According to the results, LC50 was calculated as 0.2 mg L-1 for 96 h.
Keywords: Tin; Silver nanoparticle; Clove; Colorimetry; UV-vis spectrophotometry; OPTICAL-EMISSION-SPECTROMETRY; FLUOROMETRIC-DETERMINATION; TIN SN4+; BEVERAGES; SENSITIVITY; TOXICITY; BISMUTH; TIN(IV); SENSOR; AGENT; Environmental Sciences & Ecology